Range of Motion Exercises and Foot Massage Assistance to Control Diabetic Neuropathy Symptom of Diabetes Mellitus Patient in Kabila Health Center Working Area - Fakhriatul Falah Falah; Ratnawati; Eka Firmansyah Pratama (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Gorontalo ranks 7th in terms of diabetes mellitus sufferers from 35 provinces in Indonesia. One area of ​​Gorontalo city that has quite a high number of Diabetes Mellitus sufferers is Kabila sub-district with a total of 147 people over the last 3 months. 90% of DM sufferers who come for examination to the Community Health Center experience symptoms of diabetic neuropathy.  Symptoms of diabetic neuropathy are a type of nerve damage that people with diabetes are prone to and cannot be cured, so patients must be taught how to control these symptoms. Therefore, this community service activity is expected to increase the knowledge, skills, and abilities of diabetes mellitus patients in carrying out ROM exercises and foot massages. This community service activity aims to train diabetes mellitus patients in carrying out foot care which includes ROM exercises and foot massage so that the patient's symptoms of diabetic neuropathy can be controlled. Apart from involving patients, Health Cadres are also trained as facilitators so that the sustainability of this activity in the community can be guaranteed. This community service begins with education regarding DM foot care, demonstration of ROM and foot massage procedures, and evaluation. From the activity, there was a decrease in the neuropathy score by 3 scores after the intervention was given, so it can be concluded that ROM assistance and foot massage can reduce complaints of neuropathy symptoms in patients.